Representaciones visuales femeninas en la cultura de consumo del mercado Femcare (2023)
Industrial design has been defined assuming the responsibility of designing manufacturing objects with practical value for societies. Although this may be a vague definition compared to contemporary limits, it must be made clear that their responsibility is much broader than it seems.